Supporting Syrian Refugee Children's Academic and Social-Emotional Learning in National Education Systems: A Cluster Randomized Controlled Trial of Nonformal Remedial Support and Mindfulness Programs in Lebanon. (June 2022) - Tubbs Dolan, Carly; Kim, Ha Yeon; Brown, Lindsay; Gjicali, Kalina; Borsani, Serena; Houchaimi, Samer El; Aber, J. Lawrence
Experimental evidence on strategies to support refugee children's integration into host-country public schools is needed. We employ a three-arm, site-randomized controlled trial to test the impact of short-term access to two versions of nonformal remedial programming infused with social-emotional learning (SEL) among Syrian refugee children in Lebanese public schools. Remedial programming with classroom climate-targeted SEL practices improved children's perceptions of public schools (effect sizes [ES] = 0.48–0.66) only. The remedial program with both classroom climate-targeted SEL and skill-targeted activities had positive impacts on children's perceptions of public schools (ES = 0.43–0.50) and on certain basic academic skills (ES = 0.08–0.14), and marginally significant positive and negative impacts on some SEL outcomes (ES = 0.16–0.31). We found no impacts of either version on children's global literacy or numeracy competence.